HYALURONIC ACID IN FACIAL FILLERS: AN AESTHETIC, DENTAL, AND FUNCTIONAL APPROACH - Lopez, Andres Santiago Quizhpi; da Costa, Elizângela Bonetto; Marçal, Igor Macêdo; Cabral, Wevellin Fernandes de Lima (Seven Editora, 2026)
The use of hyaluronic acid (HA) fillers has become one of the most prevalent interventions in orofacial harmonization, allowing for the restoration of facial volumes and contours with high predictability. This narrative review analyzes recent scientific evidence on the aesthetic and functional approach of HA in dentistry. Clinical success depends on understanding the material’s rheological properties, such as the elastic modulus (G’) and cohesiveness, which are essential for selecting the appropriate product for each anatomical region—from structural support in malar areas to the necessary flexibility in dynamic zones such as the lips. The study highlights the importance of standardized methodologies, such as MD Codes, which minimize technical variability and prioritize the emotional attributes of the face. The emerging role of oral HA supplementation as an adjunct to tissue health is also discussed. It concludes that the integration of in-depth anatomical knowledge and careful material selection allows the dentist to obtain natural and safe results, respecting the aesthetic-functional unity of the face. DOI: https://doi.org/10.56238/sevened2026.003-002